Shaking Criminal Incentives - Yu Aoki; Theodore Koutmeridis (Institute of Labor Economics (IZA), 2019)
We study criminal incentives exploiting the devastating shock of the 1995 Kobe earthquake. Evidence shows that the earthquake decreased burglaries but left other crime types unaffected. The effect stays significant even after controlling for unemployment, policing and income. We corroborate this by instrumenting damages with the distance from the earthquake epicentre. These findings survive various robustness checks under different specifications. The evidence is consistent with a simple theory of crime, value and specialization. We conclude that burglars respond to damages that devaluate their prospective takings. Yet, they cannot shift their specialization and substitute burglaries with other crime types.
Keywords: K42; 330; crime; burglary; value; housing damage; specialization